Longitudinal Properties of High Energy Collisions. (May 2015) - Deppman, A; Marques, L; Cleymans, J
Abstract: The rapidity distribution and longitudinal energy distribution are analysed within the thermodynamical formalism with the non-extensive Tsallis statistics. Our approach is based on a model for fireball rapidity distribution recently proposed where the fireball moves longitudinaly according to a q-Gaussian function rapidity distribution. We show that the rapidity distribution of charged hadrons are correctly obtained as compared to the experimental data for rapidities up to ∼ 10.5. The energy density as a function of the rapidity is studied for the first time. We show that most of the energy carried by hadrons are in the high rapidity region. Our results show that the energy density is a good tool for studying the logitudinal aspects of high energy collisions.